PENINGKATAN HASIL BELAJAR MODEL TGT BERBANTUAN MEDIA ULAR TANGGA DI SEKOLAH DASAR - Rosanti, Siti; Ari Pratiwi, Ika; Rustanto, Muhamad; Eko Budiono, Ahmad (Satya Widya, 2025)
This study aims to improve Civic Education learning outcomes through the implementation of the Team Games Tournament (TGT) learning model, supported by snakes and ladders game media, among sixth-grade students at SD 3 Wergu Wetan. The research was conducted as Classroom Action Research (CAR), employing the Kemmis and McTaggart model over two cycles. The participants were 26 Grade VI students. Data were collected through observations, questionnaires, and tests. Initial assessments revealed that most students had kinesthetic and visual learning styles, indicating the need for active and engaging learning strategies. During the pre-cycle phase, conventional teaching methods resulted in a classical mastery level of only 65%. After applying the TGT model with the snakes and ladders game in Cycle I, the mastery level increased to 77%. Further improvements were made in Cycle II to address issues such as unequal participation among group members. In Cycle II, classical mastery reached 85%, with a notable increase in students’ average scores. The TGT model, when combined with game-based learning, fostered an enjoyable, competitive, and collaborative classroom environment. Students became more active, confident, and enthusiastic throughout the learning process. The findings indicate that this approach effectively enhances students’ cognitive learning outcomes, motivation, and participation in Civic Education. Therefore, implementing the TGT model supported by the snakes and ladders game proves to be an effective strategy for improving the quality of Civic Education instruction at the elementary school level.